Endocrine-Disrupting Compounds in Fish Physiology, with Emphasis on their Effects on the Arginine Vasotocin/Isotocin System - Kalamarz-Kubiak, Hanna (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background and Objectives: The purposes of this review are to promote better use of existing knowledge of marine pollutants, especially endocrine-disrupting compounds (EDCs), and to draw attention to the slow progression of the research on the influence of those compounds on arginine vasotocin/isotocin system (AVT/IT) in fish. EDCs are leading to the degradation of fish habitats, reducing their spawning potential and possibly their population parameters (e.g. growth, maturation), by preventing fish from breeding and rebuilding their populations. Therefore, searching for new welfare indicators such as AVT and IT and developing research procedures mimicking environmental conditions using a versatile fish model is extremely important. Discussion: Fish species such as zebrafish (Danio rerio) and round goby (Neogobius melanostomus) can be recommended as very suitable models for studying estrogenic EDCs on the AVT/IT system and other hormones involved in the neuroendocrine regulation of physiological processes in fish. Conclusion: These studies would not only improve our understanding of the effects of EDCs on vertebrates but could also help safeguard the well-being of aquatic and terrestrial organisms from the harmful effects of these compounds.
Keywords: anthropogenic chemical pollutants